EKSPLORASI NEMATODA ENTOMOPATOGEN PADA BEBERAPA WILAYAH DI JAWA TIMUR - -, Nugrohorini (MAPETA, 2010)
Entomopatogenic Nematodes is the biological insecticides can be used to control Lepidoptera, Coleopteraand Diptera order.The nematodes can be isolated from soil of several locations in East Java. The aim of theresearch is to know the genera of entomopathogenic nematodes and population density of that nematodes from each location in East Java. The methods of the research are nematodes isolation with baiting methods, identification and count of nematodes population density. The result of the research showed that the entomopathogenic nematodes Isolate was found from Jember, Malang, Mojokerto, Sidoarjo. The genera of all nematodes Isolate is Steinernema sp. The higest population of Entomopatogenic Nematodes was found from Malang Isolate.Keyword : Entomopatogenic Nematodes, biological insecticides, Steinernema sp., population density, Isolate.